Patients’ sensory perception and satisfaction with use of metered dose inhalers and dry powder inhalers in moderate persistent asthma - Gupta, Mahesh C.; Khanna, Jyoti; Chaudhry, Dhruva (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Inhalers containing corticosteroid and a long acting β2 agonist (LABA) are widely used in asthma treatment. This study assessed the patient sensory perception and satisfaction of budesonide/formoterol fixed dose combination by pressurized metered dose inhalers (pMDI) with spacer and dry powder inhalers (DPI) in patients of moderate persistent asthma. Methods: This was a 6 week prospective, randomized, open label, comparative, parallel group clinical study. All patients had a forced expiratory volume in 1 second (FEV1) of 60-80% predicted normal. The patients were assessed for sensory perception and satisfaction in group I (pMDIs with spacers) and group II (DPIs) using patient evaluation questionnaire (PEQ) and patient satisfaction and preference questionnaire (PASAPQ) at the end of 6th week. Results: In PEQ, statistical analysis of the mean attribute ratings showed that both the devices were easy to use by patients. More medication was felt reaching throat using DPIs. Patients on DPI liked the taste and felt it to be less strong than patients on pMDIs. The overall liking was statistically comparable in two groups. In PASAPQ, the patients on DPI group were very satisfied with the treatment than pMDI (p<0.05). Conclusion: Overall liking of both DPIs and pMDIs was comparable and patients on DPI were satisfied more with the treatment device. Patient sensory perception and satisfaction may be taken into account in selecting device to improve compliance to treatment.